A Study of Learning Achievement on Learning Unit of Creative art Thinking and Creativity of Prathomsuksa Four Students by Synectices Instruction and Invention Surrealism Art - Ketlekha, Waraporn; Jongkonklang, Sirinat (Ratchaphruek Journal, 2014)
The purposes of this research were:1) to study of learning achievement; 2) to compare learning achievement between pre- and post-learning; 3) to compare learning achievement of post-learning with 75% criteria on Artistic Creative Thinking Unit; 4) to study Creative thinking; and 5) to compare Creative thinking between pre- and post-learning by using synectics instruction and invention surrealism art. The sample was 24 grade forth students who were in the second semester of 2013 academic year of Chumchon Ban Koksawai School, under office of Nakhon Ratchasima Educational Service Area Office 5. The research tools consisted of the following experimental items; 8 lesson plans of Art subject group, 30-item of learning achievement test and creative thinking test. The statistical of the data was based on the mean ( ), percentage, standard deviation (S.D.) and t-test The results of the study: 1. The learning achievement of grade forth students has shown its mean of 25.75 and standard deviation (S.D.) of 2.28 2. The learning achievement of grade forth students after using synectics instruction and invention surrealism art was higher than before using it with statistical significance at .05 level. 3. The learning achievement of grade forth students after using synectics instruction and invention surrealism art showed the 75% of criterion and not higher than the standard with statistical significance at .05 level 4. The creative thinking of grade forth students after using synectics instruction and invention surrealism art has mean of 18.54 and a standard deviation of 6.35 in the achievement. 5. The creative thinking of grade forth students after using synectics instruction and invention surrealism art was higher than the before using it with statistical significance at .05 level.